Absolute Wonder Woman. Vol. 1, The last Amazon. - Thompson, Kelly, 1976- (DC Comics, 2025)
Without the island paradise, without the sisterhood that shaped her, without a mission of peace...she's still the Absolute Amazon! Spiraling out of the catastrophic events of Absolute Power, a new side of the DC Universe is born--the Absolute Universe! In a different, darker world, Diana of Themyscira was not raised in paradise, but instead was exiled to the underworld as a baby and raised by an enemy. Darkness and exile did not destroy her; instead, they made her all the stronger--honed into an even greater weapon by tragedy, danger, and magic. Long denied her Amazonian heritage, Diana has finally reached the time for her to rejoin the surface world. Armed with new weapons forged in Hell, and a mission that looks a bit more like justice than peace, Diana will not be stopped on her quest to save the world and discover her place in it, even if that means carving it herself! Eisner Award-winning writer Kelly Thompson is joined by breakout superstar artist Hayden Sherman to reinvent Wonder Woman from the ground up! Collects Absolute Wonder Woman #1-7.